Kajian Kontribusi Sektor Pertanian Terhadap Produk Domestik Regional Bruto Di Kabupaten Labuhan Batu Tahun 2018- 2022 - Fanny Asyifa Br. Lumban Tobing; Marliyah Marliyah (Journal Economic Excellence Ibnu Sina, 2024)
Labuhan Batu Regency is famous for its abundant palm oil production, this influences the agricultural sector in supporting the economic growth of a region. The aim of this research is to analyze the contribution of the agricultural sector to the District's PDRB. Labuhan Batu and what factors influence the contribution value. The research method used is quantitative research using a descriptive approach and contribution analysis method to determine the contribution of the agricultural sector to the PDRB of Labuhan Batu Regency. The results obtained by the agricultural sector on the PDRB of the District. Labuhan Batu experienced an increase with an average of around 42% during the 2018-2022 period. Significantly, the contribution of the agricultural sector is influenced by several factors such as government spending, investment and labor which have a positive relationship with the contribution of the agricultural sector.